O 16 de setembro sob a ótica da DIPBA - Dirección de Inteligencia de La Policía de la Provincia de Buenos Aires (1990-1996) - Tolentino, Marcos Oliveira Amorim, 1986- (2012)
Orientador: José Alves de Freitas Neto